Ordinance no. 1183, §§ 1-2, TACOMA, REVISED CHARTER AND ORDINANCES (Western Blank Book Co. 1898). - (:unkn) unknown (My University, 1897)
No person within the limits of the city of Tacoma shall use, or attempt ot [sic] use, the instrument or contrivance commonly known as a slingshot, used for the purpose of throwing or propelling stones.
Keywords: DISCHARGE - NON-GUN ARMS